DETERMINAN AKURASI PELAPORAN ASET DAERAH - Haryanto, Haryanto (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2014)
This study examines empirically internal factors (knowledge and ethical perception) and externalfactors (obedience pressure and task complexity) on accuration of asset reporting that wasprepared by pengguna barang/kuasa pengguna barang. Sample of the study used sixty onesamples to the pengguna barang/kuasa pengguna barang who took duty on local governmentin Indonesia. Convinience sampling method is used as sampling method. This study usedquesionaire that were given directly to the pengguna barang/kuasa pengguna barang. Theanalyzis method was used in this study is double regression analysis. The study shows resultthat external factors (obedience pressure and task complexity) has no significant influence onaccuration of asset reporting that was prepared by pengguna barang/kuasa pengguna barang.However the internal factors (knowledge and ethical perception ) has significant influence onaccuration of asset reporting that was prepared by pengguna barang/kuasa pengguna barang.